Academically gifted adolescents' social purpose. (2nd January 2020) - Lee, Seon-Young; Matthews, Michael; Shin, Jongho; Kim, Myung-Seop
ABSTRACT: In this study, we examined the perceptions of over 1, 600 gifted and typically developing (not identified as gifted) secondary students from South Korea and the USA to identify gifted adolescents' preferred modes of social purpose, interest in and engagement with their communities, and actual commitment to societal improvement. We then examined the extent to which their social purpose varied with gifted identification status and students' cultural background. Gifted students identified actualized purpose as their preferred mode of expressing social purpose, while typically developing students favored self-oriented life goals. The gifted students also had a stronger interest in social matters and showed a greater awareness of social and civic engagement than the nonidentified students did. Among the gifted students, Korean students expressed a stronger belief in prosocial behaviors and reported a greater commitment to what they believed important for society. In contrast, the American adolescents behaved in accordance with their expressed values. Both perceived social purpose and commitment to their communities and society predicted students' life satisfaction regardless of cultural affiliation. Discussion focuses on differences in the degree of prosocial intention and engagement between the gifted and typical students, and personal and societal values that may help explain the differences we observed in social purpose among the gifted students from the two different nations.